The essence and purpose of the social state in the context of the legal experience of modern Ukraine: theoretical and legal analysis - S. S. Polesov (Bulletin of Kharkiv National University of Internal Affairs)
The concept of the social state is one of the elements of the constitutional identity of Ukraine. In the context of the Constitution of Ukraine, the social state is endowed with a number of important legal features and characteristics that can be distinguished on the basis of a systematic analysis of constitutional norms, where the concept of the social state is directly mentioned. This concept is included among the fundamental legal characteristics of the Ukrainian state and, at the same time, among the defining characteristics of the Ukrainian constitutional system. It is presented in the Constitution of Ukraine in an extremely generalized form, without specifying the manifestations of the social state, its features, functions, tasks, etc. The characteristics of the Ukrainian state as a social state cannot be changed in any other way than by amending the Constitution of Ukraine in a particularly complicated constitutional procedure. Any changes in the constitutional and legislative organization of state power or in its implementation should not take place if they are inconsistent with the legal nature of Ukraine as a social state, or directly or indirectly contradict the essence and purpose of the social state as such.